2019
DOI: 10.1093/eurheartj/suz205
|View full text |Cite
|
Sign up to set email alerts
|

The burden of comorbidities in pulmonary arterial hypertension

Abstract: Patients with comorbidities are often excluded from clinical trials, limiting the evidence base for pulmonary arterial hypertension (PAH)-specific therapies. This review aims to discuss the effect of comorbidities on the diagnosis and management of PAH. The comorbidities discussed in this review (systemic hypertension, obesity, sleep apnoea, clinical depression, obstructive airway disease, thyroid disease, diabetes, and ischaemic cardiovascular event) were chosen based on their prevalence in patients with idio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 71 publications
1
55
0
2
Order By: Relevance
“…3,4 Elderly patients with PAH have a higher rate of comorbid conditions compared with younger patients, introducing more complications into their treatment due to considerations such as polypharmacy and drug-drug interactions. 5 Although research has indicated that comorbidities negatively affect outcomes in patients with PAH, there is limited information regarding the effect of comorbidities on survival in elderly patients. 6,7 Evidence is also sparse on the mortality benefit of PAH therapy in elderly patients not only because the low prevalence of PAH makes it unfeasible to recruit sufficient patients of any age to detect survival differences in a randomized controlled trial (RCT) but also because elderly patients with multiple comorbidities are typically excluded from PAH RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Elderly patients with PAH have a higher rate of comorbid conditions compared with younger patients, introducing more complications into their treatment due to considerations such as polypharmacy and drug-drug interactions. 5 Although research has indicated that comorbidities negatively affect outcomes in patients with PAH, there is limited information regarding the effect of comorbidities on survival in elderly patients. 6,7 Evidence is also sparse on the mortality benefit of PAH therapy in elderly patients not only because the low prevalence of PAH makes it unfeasible to recruit sufficient patients of any age to detect survival differences in a randomized controlled trial (RCT) but also because elderly patients with multiple comorbidities are typically excluded from PAH RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…The patient was started on oral therapy with calcium channel blockers for vasoreactive PAH, along with disease modifying drugs for SSc with mycophenolate, steroids, prostacyclin receptor agonist, endothelin receptor antagonist, diuretics, steroids, reinforcing compliance with CPAP for OSA, optimization of medications for heart failure, and continuing treatment for anemia and MDS. Such multifactorial cases with PAH, should also focus on management of co-morbidities with a multidisciplinary team approach to optimize management from every aspect of contributing factors [ 5 - 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic hypertension, ischaemic heart disease, dyslipidaemia, diabetes, and arrhythmia are among the most common comorbidities reported in older patients, 21 , 27 , 28 and they are more prevalent in this population compared with younger adults, as evidenced across two studies that defined older as >50 years of age, 21 and ≥75 years of age 27 . Comorbid cardiovascular and metabolic diseases are also commonly observed in the general PAH population 24 and management of PAH in these cases is fully discussed in a separate review in this supplement 29 …”
Section: Diagnosis Of Pulmonary Arterial Hypertension In Older Patientsmentioning
confidence: 96%